Biodiversity pattern of fish assemblages in Poyang Lake Basin: Threat and conservation. Issue 20 (26th September 2019) - Liu, Xiongjun; Qin, Jiajun; Xu, Yang; Zhou, Min; Wu, Xiaoping; Ouyang, Shan
Abstract: Poyang Lake Basin is of great importance to maintain regional ecological balance. However, fish biodiversity in this basin has rapidly declined as the result of anthropogenic habitat alteration, such as dam construction, sand mining, and water pollution. Here, we aimed to analyze the temporal and spatial changes in biodiversity patterns of fish in Poyang Lake Basin over the last 37 years. The number of fish species underwent a significant decrease in the current period. In particular, 36.7% of the migration of fish was extirpated. Twenty‐seven fish species have been formally assessed using the Chinese Red List were currently listed as Critically Endangered (9), Endangered (3), Vulnerable (10), and Near Threatened (5). Alpha and gamma diversity revealed that fish diversity had also decreased, and beta diversity showed significant composition dissimilarity in two periods. PCoA showed that the historical fish composition dissimilarity was significantly different from that of the current period. We found a significant effect of the geographical distance on the spatial turnover component for the historical and current periods. In addition, the nestedness component was the main contributor to beta diversity, which indicated one large protected area should be established in Poyang Lake and the Ganjiang River Basin with higher species richness. These results indicated that fish biodiversity declined in the current period likely caused by anthropogenic habitat alteration and other threatened factors. Therefore, we suggest that the habitat reconstruction and biodiversity conservation for fish have become imperative in this basin, and a complete management plan should be carried out. Abstract : Poyang Lake Basin is of great importance to maintain regional ecological balance. However, fish diversity in this basin has rapidly declined as the result of human activities. Here, we aimed to analyze how temporal and spatial changes impact biodiversity patterns of the fish assemblages in Poyang Lake Basin over the last 37 years. The diversity of fish species underwent a significant decrease. In particular, 36.7% of the migration of fish was extirpated. Twenty‐seven fish species have been formally assessed using the Chinese Red List were currently listed as Critically Endangered (9), Endangered (3), Vulnerable (10), and Near Threatened (5). Alpha and gamma diversity revealed that fish diversity had also decreased, and beta diversity showed a significant trend toward taxonomic homogenization. PCoA showed that the historical fish composition similarity was significantly different from that of the current period. These results indicated that human activities have seriously affected the fish habitat and led to the decline in fish diversity.